A point-free perspective on lax extensions and predicate liftings - Goncharov, Sergey; Hofmann, Dirk; Nora, Pedro; Schröder, Lutz; Wild, Paul (Mathematical Structures in Computer Science, 2023)
Lax extensions of set functors play a key role in various areas, including topology, concurrent systems, and modal logic, while predicate liftings provide a generic semantics of modal operators. We take a fresh look at the connection between lax extensions and predicate liftings from the point of view of quantale-enriched relations. Using this perspective, we show in particular that various fundamental concepts and results arise naturally and their proofs become very elementary. Ultimately, we prove that every lax extension is induced by a class of predicate liftings; we discuss several implications of this result.
CRIS-Team Scopus Importer:2023-12-15
Keywords: coalgebraic modal logic; Kantorovich extension; Lax extension; Moss lifting